Activation of NF-κB signaling pathway in HSV-1-induced mouse facial palsy: Possible relation to therapeutic effect of glucocorticoids. (19th March 2015) - Liu, W.; Fan, Z.; Han, Y.; Xu, L.; Wang, M.; Zhang, D.; Mao, Y.; Li, J.; Wang, H.
Highlights: HSV-1 induces facial paralysis of mice and activates NF-κB in the paralyzed mice. NF-κB activation stimulates the expression of TNF-α and COX-2 in the paralyzed mice. Glucocorticoids inhibit NF-κB activation in the paralyzed mice. Glucocorticoids down-regulate the expression of NF-κB inducible TNF-α and COX-2. Abstract: It has been documented that infection of herpes simplex virus type 1 (HSV-1) contributes to the initiation of Bell's palsy. However, the exact mechanisms responsible for this disorder have not been fully elucidated to date. A mouse model of facial palsy induced by HSV-1 provides an opportunity to investigate the alteration in activities of nuclear factor-kappa B (NF-κB) and its consequent effect on two key inflammatory factors, i.e., tumor necrosis factor (TNF)-α and cyclooxygenase-2 (COX-2), as well as the effect of glucocorticoids (GCs) in this work. I-kappa B (IκB)-α phosphorylation and NF-κB nuclear translocation were measured by western blotting, and NF-κB/DNA binding activity was assessed by electrophoretic mobility shift assay (EMSA). Results showed the IκB-α phosphorylation and degradation as well as NF-κB activation in a time-dependent manner. The expression of TNF-α and COX-2 were determined by real-time polymerase chain reaction (PCR), western blotting and/or enzyme-linked immunosorbent assay (ELISA) respectively. Concomitant with the activation, the expression and secretion of TNF-α and COX-2 were rapidly induced in HSV-1-infected paralyzed mice. Conversely, the activation of NF-κB and up-regulation of TNF-α and COX-2 were blocked by pretreatment with NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC) before being inoculated with HSV-1 to mice. In addition, GCs inhibited the nuclear translocation and DNA binding activity of NF-κB via inhibiting IκB-α degradation. Meanwhile, TNF-α production and COX-2 expression were significantly reduced by GCs. In conclusion, HSV-1 inoculation induced the activation of NF-κB, expression and secretion of TNF-α and COX-2 in the facial paralyzed mice, while, glucocorticoid effectively down-regulated TNF-α and COX-2 expression in HSV-1-induced paralyzed mice.